NATIONAL INDUSTRY AND ITS ROLE IN THE COUNTRY’S ECONOMY - Г. А.Хамдамова (Galaxy International Interdisciplinary Research Journal, 2023)
This article discusses the dynamics of the development of the diversified industry of the Republic of Uzbekistan, the results of the state strategy and policy of modernization and diversification of production, as well as the results of significant structural changes in the country’s economy.